Performance of nano kaolin clay modified bitumen under aging through the viscosity - Mohd Warid, M. N.; Al-Saffar, Z. H.; Putra Jaya, Ramadhansyah; Masri, K. A.; Muzamir, Hasan; Mudjanarko, S. W. (IOP Science, 2021)
Increasing traffic volumes and rising cost of bitumen making it necessary to improve the performance of binder through bitumen modification. Nano particle have emerged as the potential solution to greatly enhance the properties of binder. This study explores the potential application of nano kaolin clay (NKC) as a modifier to improve the performance of bitumen incorporating different percentages of NKC. The performance of NKC modified bitumen was assessed using a viscosity and ageing test. The average size of NKC used was 57.7 nm. Then, 0% (control), 3%, 5%, 7% and 9% NKC by weight of bitumen PEN 60/70 was added. Generally, the results reveal that bitumen binder including nano kaolin clay is more effective in improvement the viscosity properties of asphalt before and after aged.